A theory of the microdynamics of occurrent thought - Demmin, Herbert S., 1959- (Lexington Books, 2015)
A Theory of the Microdynamics of Occurrent Thought presents what is, perhaps, the first comprehensive theory of the microdynamics of occurrent thought to be presented in the psychological, cognitive, and philosophical literatures.